Kangaroo: The Australian Story. Issue 5 (3rd September 2017) - Verevis, Constantine
Abstract: In October 1950, the Adelaide Advertiser ran an article titled "Hollywood Insists on Kangaroos" (page 7). The story begins: "If you've got—or know of—any kangaroos who would like to become movie actors, send them to Director Lewis Milestone, Port Augusta, South Australia. He needs them to play themselves in the 20th Century-Fox production Kangaroo ." The article continues, explaining that producer Robert Bassler was looking to secure at least 300 kangaroos for the picture's "most thrilling scene", one without which the picture would lose much of its international appeal. Specifically, the script called for hundreds of thirst-crazed kangaroos to descend on a last remaining waterhole and put up a terrific battle for the water. In the same newspaper article, Bassler admitted that he didn't exactly know how the scene would be accomplished, but said: "[T]he sequence … will be the most unique thing ever put on the screen. It could become the most talked-about scene in the history of movies." This essay looks to the production and reception contexts of Kangaroo to consider some of the benefits and dangers of global film culture, and the difficulties of and possibilities for Australian (international) pictures in the post-war years.